Phospholipid molecular species composition of Chinese traditional low-salt fermented fish inoculated with different starter cultures. (September 2018) - Zang, Jinhong; Xu, Yanshun; Xia, Wenshui; Jiang, Qixing; Yang, Fang; Wang, Bin
Abstract: Phospholipid molecular species composition of Chinese traditional low-salt fermented fish (Suan yu) inoculated with different starter cultures was investigated. Fifty-six molecular species of phospholipid including 20 species of phosphatidylcholine (PC), 15 species of phosphatidylethanolamine (PE), 6 species of phosphatidylserine (PS), 9 species of lysophosphatidylcholine (LPC), and 6 species of lysophosphatidylethanolamine (LPE) were identified using ultra-performance liquid chromatography with quadrupole-time-of-flight mass spectrometry (UPLC-Q-TOF-MS). PC (C16:0–C18:1), PE (C16:0–C22:6), PS (C15:0–C22:6), LPC (C22:6) and LPE (C22:5) were the predominant species. Bioactive polyene phospholipids mainly existed in PE. Furthermore, starter cultures exhibited different influence on phospholipid molecular species. Compared to naturally fermented Suan yu, more molecular species of PE and PS as well as polyene phospholipids were detected in the samples inoculated with Saccharomyces cerevisiae 31 and mixed starter cultures. Graphical abstract: Unlabelled Image Highlights: The phospholipid molecular species of fermented fish were identified by UPLC -MS. The PE profiles were characterized by ω3 PUFA, such as EPA, DPA and DHA. The bioactive polyene phospholipids mainly existed in PE. The PE composition was more affected by Saccharomyces cerevisiae 31 than PC.